Feasibility of Palm Sugar (Arenga pinnata Merr.) Business by the Community in Betteng Village, Majene Regency - Ritabulan; Sarwanto (Pangale Journal of Forestry and Environment, 2021)
Sugar palm (Arenga pinnata Merr) is one of non timber forest products (NTFPs) which are widely used and cultivated to fulfill the dayly nedds of the community. This study aims to determine and analyse the feasibility of sugar palm business by community who living and around the forest. The location of this study was in Betteng Village, Pamboang District, Majene Regency. The data analysis was carried out through qualitative deskriptif analysis and quantitative analysis. The result showed that the palm sugar business in Betteng Vilage was feasible to developed with R/C value was 2.50.